Crash detection and emergency response (CraDER) system / Adam Luqman Roslan - Roslan, Adam Luqman (2024)
Several road accident victims who survived the accident could not be saved since help arrived late owing to serious injuries and there were also accident victims who were trapped in cars that caught fire because of the accident. The aim of this project is to design a system that can detect crash of vehicles and emergency response during the accident. The project has been developed by using Arduino Uno, Accelerometer, Flame Sensor, GPS Module, GSM Module, and automatic fire suppression. The process of this project starting with the input received by the Accelerometer for the crash detection, then if accident occur, the GPS Module will detect the location and send the location to the GSM Module where it will send notification to alert the people on their smartphone through SMS. The Flame Sensor is used if the flame or spark presence around the vehicles and if the flame presence, it will trigger the ABC Dry Powder to spread the ABC dry powder to the certain part of the vehicles. This system will help to solve the problem that occurs during an accident to save the lives of people and prevent the vehicles from being burned. Arduino Uno, Accelerometer, Flame Sensor to improve the accident detection and emergency system. CraDER System focused on developing a system tool that can assist accident victims and function as a preventative measure to stop vehicle fires and more serious injuries from occur. This project contribution focusing on society where most of the people use vehicles as a transport from one place to the destination every day